Socio-economic features of planning the volume of specialized dermatological care in the Sverdlovsk region ("Journal "U". Economy. Management. Finance.", 2024)
In the article, the authors consider modern socio-economic features of planning the volume of dermatological medical care to the population of the Sverdlovsk region, taking into account the current local conditions of the industrial region. Based on a comparative analysis of the activities of the Ural Research Institute of Dermatovenereology and Immunopathology, the authors identified priority areas for the development of dermatological medical care within the framework of the program of state guarantees to the population of the Russian Federation, taking into account the regional features of the development of the Sverdlovsk region. Based on the results obtained, the author’s conclusion is formulated about a differentiated approach in the system of planning specialized medical care, taking into account available economic resources.
Keywords: economic resources; planning; medical care; social and economic efficiency; economic management methods